Legal Shifts in Credit Agreements Amid Covid-19: A Contextualized Analysis from Islamic Economic Law - Haris Yusuf; Anwar Borahima; Ahmadi Miru; Nurfaidah Nurfaidah; Souad Ahmed Ezzerouali (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
The Covid-19 pandemic, has caused a global crisis affecting not only health but also legal and financial systems, particularly the sector of financing based on credit agreements. The widespread inability of debtors to fulfill their financial obligations raised fundamental questions regarding the validity and enforceability of contractual relationships, both in conventional and Islamic legal frameworks. This study aims to examine the legal shift in the implementation and adjustment of Shariah-compliant credit contracts during the pandemic and to assess the applicability of Islamic legal principles such as al-‘udhr (legal excuse), maslahah mursalah (public interest), and al-taysir (facilitation) as normative bases for contract renegotiation and restructuring. Using a normative-qualitative method, the research analyzes legal texts, fatwas issued by the DSN-MUI, and state regulations such as those issued by the OJK. The findings indicate that the pandemic constitutes a force majeure event that can legally justify contract modification within Islamic jurisprudence. The study concludes that a contextual and adaptive approach rooted in maqāṣid al-sharī‘ah offers both normative legitimacy and practical effectiveness in times of crisis. It also recommends developing a flexible contractual model that harmonizes Shariah principles with national legal standards, thereby ensuring justice, legal certainty, and resilience in Islamic financial institutions.